2009
DOI: 10.1051/0004-6361/200912582
|View full text |Cite
|
Sign up to set email alerts
|

Visible spectroscopy of the new ESO large programme on trans-Neptunian objects and Centaurs: final results

Abstract: Context.A second large programme (LP) for the physical studies of TNOs and Centaurs, started at ESO Cerro Paranal on October 2006 to obtain high-quality data, has recently been concluded. In this paper we present the spectra of these pristine bodies obtained in the visible range during the last two semesters (November 2007−November 2008) of the LP. Aims. We investigate the spectral behaviour of the TNOs and Centaurs observed, and we analyse the spectral slopes distribution of the full data set coming from this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 41 publications
8
47
3
Order By: Relevance
“…Barucci et al (2006) already observed it spectroscopically and detected water ice and clear evidence of methanol in its surface. Fornasier et al (2009) (90377) Sedna, and different from the previous visible observations reported by Barucci et al (2006), for which the computed slope was 27.9 ± 0.1%/(10 3 Å). The period is not well known, Ortiz et al (2006) reported a noisy lightcurve with a small amplitude of about 0.08 with possible periodicities of 6.76 or 9.47 hrs.…”
Section: Introductioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Barucci et al (2006) already observed it spectroscopically and detected water ice and clear evidence of methanol in its surface. Fornasier et al (2009) (90377) Sedna, and different from the previous visible observations reported by Barucci et al (2006), for which the computed slope was 27.9 ± 0.1%/(10 3 Å). The period is not well known, Ortiz et al (2006) reported a noisy lightcurve with a small amplitude of about 0.08 with possible periodicities of 6.76 or 9.47 hrs.…”
Section: Introductioncontrasting
confidence: 80%
“…Using the new constraints of the albedo value, we model the complete set of new available spectra as well the previous published data A&A 539, A152 (2012) Fornasier et al (2009). to investigate the surface composition properties and search for surface variation.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the data have been published for this object. Photometry in both wavelength ranges has been presented in Perna et al (2010) while results based on visible spectroscopy have been presented in Fornasier et al (2009) Table 1. Seventeen exposures of 600 s were taken in a jitter pattern, for a total exposure time of 2 h 50 min.…”
Section: Data Of the Object 2007 Vh 305mentioning
confidence: 99%
“…Near-infrared photometry from Gemini+NIRI (this work) and near-infrared published colors from Orcus. Fornasier et al (2009). The three top spectra were shifted by 0.5 in reflectance for clarity.…”
Section: Visible Datamentioning
confidence: 99%
“…6), we draw a similar conclusion for the case of Orcus. (208996) (208996) has a quasi-neutral featureless spectrum in the optical, with a spectral slope of 1.6 ± 0.6%/100 nm (Fornasier et al 2009, and references therein). Guilbert et al (2009) confirmed the presence of water ice (Barkume et al 2008) in its crystalline phase from near-infrared spectroscopy, and noted a possible absorption feature around 2.3 μm.…”
Section: Charonmentioning
confidence: 99%